Reformasi Hukum Acara Penyidikan di Era Digital: Analisis Kesesuaian KUHAP dan KUHP Baru terhadap Kebutuhan Teknologi Informasi dalam Perspektif Ketatanegaraan - Silalahi, Wilma; Antonio, Michelle Linda (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The reform of criminal investigation procedures has become a crucial aspect of Indonesia’s criminal justice system renewal, particularly following the enactment of the new Criminal Code, which introduces significant shifts regarding the rights of suspects, investigative authority, and the implementation of due process of law. In an era of rapid digital development, investigative practices must also incorporate the principles of good governance and human rights protection to ensure that state authority is exercised proportionally. This study aims to analyze the relevance of the principles of good governance in modern investigative processes, assess the adequacy of due process guarantees under the current Code of Criminal Procedureand the new Criminal Code, and identify practical challenges in application. Using a normative legal research method through statutory, conceptual, and comparative approaches, the study finds that criminal investigations in Indonesia continue to face issues such as normative inconsistency, regulatory disharmony, and weak accountability mechanisms. The integration of the principles of good governance has the potential to strengthen the quality and fairness of investigations, yet requires clearer normative foundations and consistent implementation. Moreover, the new Criminal Code does not fully resolve harmonization issues with Code of Criminal Procedure, making procedural reform an urgent necessity. The findings contribute to the enhancement of suspect protection, professionalism among investigators, and the overall improvement of Indonesia’s criminal justice system.